2014
DOI: 10.1016/j.redox.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO, NOx and SO2 on ROS production, photosynthesis and ascorbate–glutathione pathway to induce Fragaria×annasa as a hyperaccumulator

Abstract: A study was conducted to determine the effect of carbon monoxide (CO), nitroxide (NOx) and sulfur dioxide (SO2) on ROS production, photosynthesis and ascorbate–glutathione pathway in strawberry plants. The results showed that both singlet oxygen (O2−1) and hydrogen peroxide (H2O2) content increased in CO, NOx and SO2 treated strawberry leaves. A drastic reduction of primary metabolism of plants (photosynthesis), with the closure of stomata, resulted in a reduction of protein, carbohydrate and sucrose content d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 39 publications
2
46
0
1
Order By: Relevance
“…The data of Ackerson and Hebert (1981) showed large starch granules in stress-adapted plants. Moreover, greater starch accumulation in plants cells was associated with the greater resistance of their photosynthetic apparatus to oxidative stress (Muneer et al, 2014). Compared to those in Xanthi, the symptoms of programmed cell death (PCD) that were observed in sections from the clomazonetreated Virginie plantlets (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The data of Ackerson and Hebert (1981) showed large starch granules in stress-adapted plants. Moreover, greater starch accumulation in plants cells was associated with the greater resistance of their photosynthetic apparatus to oxidative stress (Muneer et al, 2014). Compared to those in Xanthi, the symptoms of programmed cell death (PCD) that were observed in sections from the clomazonetreated Virginie plantlets (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of SO 2 diffusion into the plant body and its effects on plant metabolism have long been established (Horsman & Wellburn, ; Kropff, ; Malhotra & Hocking, ; Muneer, Kim, Choi, Lee, & Lee, ; Thomas, Hendricks, & Hill, ). However, the action of SO 2 in inducing stomatal closure remains concealed.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis that is accompanied with DNA laddering can occur as hypersensitive response to incompatible pathogens and O 3 -induced hypersensitive response-like lesion (Pasqualini et al, 2003;Reape, Molony, & McCabe, 2008). TUNEL assay detecting DNA laddering of the chromosome was conducted on guard cells treated with 2 hr of H 2 SO 3 to explore whether the cell death was apoptotic or not The mechanism of SO 2 diffusion into the plant body and its effects on plant metabolism have long been established (Horsman & Wellburn, 1977;Kropff, 1991;Malhotra & Hocking, 1976;Muneer, Kim, Choi, Lee, & Lee, 2014;Thomas, Hendricks, & Hill, 1950). However, the action of SO 2 in inducing stomatal closure remains concealed.…”
Section: H 2 So 3 Induces Nonapoptotic Cell Deathmentioning
confidence: 99%
“…A recent study in strawberry ( Fragaria × ananassa ) investigating plant responses after treatment with different low, medium and high doses of CO (133–533 ppb), NO x and SO 2 (0.05–0.20 ppm) showed that prolonged exposure to the pollutants resulted in continuous ROS production in leaves, with a negative effect on stomatal closure and photosynthesis (Muneer et al . ). While antioxidant enzyme activity increased at low doses, it decreased during exposure to high doses, possibly reaching the total capacity limit of the plant defence response.…”
Section: Plant Physiological and Molecular Responses To Combinations mentioning
confidence: 97%
“…As we will discuss, air pollutants can have multiple negative effects on plant biochemical and physiological processes, with effects that are always dose‐dependent (Muneer et al . ) and usually result in visible symptoms in leaves. According to these dynamics, exposure to mixtures of air pollutants can induce responses in the plant at several levels.…”
Section: Introductionmentioning
confidence: 99%